A novel analytical performance investigation of varying water depth in an active multi-stage basin solar still in addition to optimization of water depth in a single stage basin still - E. Davani; K. Jafarpur; M.R. Karimi Estahbanati (Energy Reports, 2023)
In the present research, active solar basin stills are studied and the effect of water depth on output productivity is evaluated analytically. In order to validate the reliability of the results of the proposed model, they have been compared with the available Karimi’s experimental data with an acceptable accuracy. Then, the temperature distribution of the basin, covers, the water in the basin and heat transfer coefficients between the water as well as covers in all stages are calculated. Then, the amount of fresh water as an output are derived for one and multistage units. With increasing the number of stages from one to four, the amount of fresh water was increased by 42%, 72% and 94%, respectively. In addition, the amount of yield water for the ratio of three stages to two stages and four stages to three stages was increased 20% and 13%, respectively. Moreover, in this article, a new approach is adapted based on the variation of water depth instead of considering it constant and because of this methodology, there is an optimum value for water depth, which leads to the maximum productivity. Due to the storage of energy in water as a function of water depth, with an increase in the amount of water in the basin of solar stills more than the optimum value, or even decreasing the water depth below the optimum value, one should expect to get the basin without water at the end of day. This may lead to have less fresh water in the output at the end of the day. Finally, a correlation has been provided to calculate the productivity of a single basin still based on the water depth in the basin.